PD-L1/PD1 Expression, Composition of Tumor-Associated Immune Infiltrate, and HPV Status in Conjunctival Squamous Cell Carcinoma - Nagarajan, Priyadharsini; El-Hadad, Christian; Gruschkus, Stephen K.; Ning, Jing; Hudgens, Courtney W.; Sagiv, Oded; Gross, Neil; Tetzlaff, Michael T.; Esmaeli, Bita (Investigative ophthalmology & visual science, 2019)
Conjunctival squamous cell carcinoma (SCC), a type of ocular surface neoplasia, is primarily treated by surgical resection and topical immuno- or chemotherapy. Metastatic disease may be treated with systemic chemo- or immunotherapy, albeit with variable response. The purpose of this study was to determine whether immune checkpoint blockade might be considered in the management of conjunctival SCC. In this retrospective study, we evaluated tumor programmed death-ligand 1 (PD-L1) expression, high-risk human papillomavirus (HPV) status, and immunohistochemical expression of cluster of differentiation 3 (CD3), cluster of differentiation 8 (CD8), and programmed death 1 (PD1) in tumor-associated immune infiltrate in a series of 31 conjunctival SCCs. PD-L1 expression in ≥1% of tumor cells was noted in 14 conjunctival SCCs (47%) and was more prevalent in invasive than in situ SCC and among tumors with higher American Joint Committee on Cancer (AJCC) T category (≥T3 versus ≤T2). The density of CD3-positive T cells was higher in primary than recurrent tumors and higher in invasive than in situ tumors. Density of CD3-positive and CD8-positive T cells was higher in higher AJCC stage tumors. Density of CD8-positive T cells was higher in HPV-positive than HPV-negative tumors. PD-L1 expression correlated with a higher density of CD3-, CD8-, and PD1-positive cells in the tumor-associated immune infiltrate but not with HPV status. Our findings demonstrate that PD-L1 is expressed in almost half of conjunctival SCCs. The density of tumor-associated immune cells correlated with invasive SCC, stage, and HPV status in conjunctival SCC. Our findings support further studies to establish the potential application of immune checkpoint blockade in the management of conjunctival SCC.